Keeping love alive as memories fade : the 5 love languages and the Alzheimer's journey - Chapman, Gary D., 1938-; Barr, Deborah; Shaw, Edward G. (Chicago : Northfield Publishing, 2016)
Across America and around the world, the five love languages have revitalized relationships and saved marriages from the brink of disaster. Can they also help individuals, couples, and families cope with the devastating diagnosis of Alzheimer's disease (AD)? Coauthors Chapman, Shaw, and Barr give a resounding yes. Their application of the five love languages creates a new way to touch the lives of the five million Americans who have Alzheimer's, as well as their fifteen million caregivers. At its heart, this book is about how love gently lifts a corner of dementia's dark curtain to cultivate an emotional connection amid memory loss. This collaborative work between a healthcare professional, caregiver, and relationship expert will: provide an overview of the love languages and Alzheimer's disease; correlate the love languages with the developments of the stages of AD; discuss how both the caregiver and care receiver can apply the love languages; address the challenges and stresses of the caregiver journey; and offer personal stories and case studies about maintaining emotional intimacy amidst AD.
A word from Gary -- Ed and Rebecca: A love story -- Love: It's all in your head -- Alzheimer's disease puts love to the test -- Every day is the best day -- Facilitating love -- Stories of Hesed -- Voices of experience -- The journey no one wants to take: Postscripts from the authors -- Ways to say I love you in middle- and late-stage dementia -- For those who want to know more.
Includes bibliographical references.
Keywords: Alzheimer's disease -- Patients -- Care; Communication; Dementia; Alzheimer's disease -- Patients -- Family relationships; Alzheimer's disease; Memory; Love; FAMILY & RELATIONSHIPS -- Eldercare; FAMILY & RELATIONSHIPS -- Life Stages -- Later Years; HEALTH & FITNESS -- Diseases -- Alzheimer's & Dementia; Religion -- Christian Life -- Love & Marriage